Citogenética e citometria de fluxo de espécies de Dorstenia (Moraceae) endêmicas da Floresta Atlântica - Fernandes, Alda Francisca Rodrigues de Sousa (2015)
Moraceae comprises latescentes plant tree size as the fig trees (Ficus), shrub species as Sorocea, or herbaceous species as Dorstenia species. The Dorstenia is the only herbaceous within the family, with about 105 species, and it has active ingredients linked to several therapeutic functions. Besides the medical use, the "carapiás", as popularly known, the Dorstenia species also have a high potential as ornamental plants. Some studies involving systematic, phylogeny, molecular and phytochemical are reported to some species of Dorstenia. However, there are few reports about the cythogenetic data and DNA content in the gender, probably due to the difficulty to find natural populations in the field and the vulnerable situation that affects most species.Cytomorphological data associated with the DNA 2C value can generate information on the chromosomal evolution and cooperate with systematic and taxonomic aspects of a group. That being said, the objective of this study was to characterize, by using cytogenetics and flow cytometry, three species of Dorstenia:. D. arifolia Lam., D. bonijesu Carauta & C. Valente and D. elata Hook. For this, the chromosomal number was determined, morphometric and intrachromosomal asymmetry (A2) parameters were established and nuclear DNA content was measured. The plant material was collected in Mata das Flores, ES. To cytogenetics, roots were obtained by using the hydroponic system, treated with APM in the concentrations of 3, 4 and 5 uM, for 16 to 18 h and fixed in methanol: acetic acid (3:1), for later digestion, coloring and observation of the slides. For flow cytometry young individuals were colected. The leaves were used as material of analysis to quantify the nuclear DNA content. The Cytogenetic methodology allowed to obtain suitable material for analysis. It was found 32 chromosomes and it was possible to mount the first karyogram to the three species. With the morphometric data, the classification of chromosomes was determined and the differences were confirmed between the three karyotypes. The A2 asymmetry index varied between the species: D. bonijesu showed A2 = 0.16, followed by D. arifolia A2 = 0.14 and D. elata A2 = 0.13. The flow cytometric analysis allowed to measure the nuclear DNA content of 2C = 3.49 picograms (pg) for D. elata, 2C = 4.05 pg for D. bonijesu , and 2C = 5.47 pg for D. arifolia. Despite of the fact that the three species have the same chromosome number (2n = 32), the DNA content values obtained by flow cytometry and the results of the asymmetric index were different. According to the A2 values and data described in the literature D. elata can be the species more derivative in relation to D. bonijesu and D. arifolia, for having the lowest asymmetry index, and the lowest content of nuclear DNA. Therefore, the present research data allowed to characterize, for the first time, three species of Dorstenia, contributing to different areas such as ecology, phylogeny, systematics and evolution.